View the step-by-step solution to:

Question

need help with this question

alt="72216094_477783886148572_8581274396038004736_n.jpg" />

72216094_477783886148572_8581274396038004736_n.jpg

Top Answer

(a) Given: f'(x) = f(x) * (ln(f(x)) Now g(x) = (f(x)) ^(e^(-x)) By taking logarithms, we get ln(g(x)) = ln[(f(x)) ^(e^(-x))... View the full answer

Sign up to view the full answer

Other Answers

Please find the attachment .... View the full answer

IMG_20191016_002055.jpg

I (x ) = y(x ) en ( six ) )
-
O
a)
9 ( n ) = y (x) e
In g ( 2 ) = In ( s (n) ex )
en ( 9(21) ) = ex In 1 (x )
Dyl. both Sides wix. tix
9 ( 2 )
9 (21) = e" f'm) - e en J ( )
= )
9 ( * )
=...

Why Join Course Hero?

Course Hero has all the homework and study help you need to succeed! We’ve got course-specific notes, study guides, and practice tests along with expert tutors.

  • -

    Study Documents

    Find the best study resources around, tagged to your specific courses. Share your own to gain free Course Hero access.

    Browse Documents
  • -

    Question & Answers

    Get one-on-one homework help from our expert tutors—available online 24/7. Ask your own questions or browse existing Q&A threads. Satisfaction guaranteed!

    Ask a Question